1997
DOI: 10.1161/01.cir.95.4.932
|View full text |Cite
|
Sign up to set email alerts
|

Automated Cardiac Output Measurement by Spatiotemporal Integration of Color Doppler Data

Abstract: Automatic integration of numerical data within color Doppler flow fields is a feasible new method for quantifying flow. It is simpler and faster, requires fewer assumptions, and uses only one apical view. ACOM is a promising new approach to echocardiographic quantification that deserves further study and refinement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
1
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(39 citation statements)
references
References 24 publications
1
35
1
2
Order By: Relevance
“…During color Doppler imaging the gray scale is clearly visible and allows the operator to exactly define the vessel walls and to set an optimal gain; the optimal gain setting was simply obtained by maximizing the gain level without random color noise in the non-flow areas (i.e. the color uniformly fills the vessel but is not seen in the adjacent walls 17 ).…”
Section: Study Group and Measurementsmentioning
confidence: 99%
“…During color Doppler imaging the gray scale is clearly visible and allows the operator to exactly define the vessel walls and to set an optimal gain; the optimal gain setting was simply obtained by maximizing the gain level without random color noise in the non-flow areas (i.e. the color uniformly fills the vessel but is not seen in the adjacent walls 17 ).…”
Section: Study Group and Measurementsmentioning
confidence: 99%
“…Automated cardiac output method has been recently developed and validated in different clinical situations [12][13][14]27]. Sun et al have clearly demonstrated that ACM is a feasible, easy and fast method [11], since it allowed to decrease time acquisition for the calculation of aortic output, as compared to the traditional Doppler method. In our study, we have demonstrated that ACM is a reliable method for the calculation of pulmonary output, with best correlations and agreements between echocardiographic and invasive pulmonary outputs obtained with ACM, as compared to the conventional PWD method.…”
Section: Discussionmentioning
confidence: 99%
“…The principle of ACM has been previously reported [11,19]. This methods allows to perform automatically the calculation of cardiac output.…”
Section: Echocardiographic Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…ACOM-MethodeAuch die ACOM-Methode ("Automated Cardiac Output Measurement") basiert wie die PISA-Methode auf einer Farb-Doppler-Geschwindigkeitsanalyse im proximalen Flussfeld[45]. Bei ihr werden jedoch die unterschiedlichen Geschwindigkeiten in einer Ebene, die senkrecht zur Flussrichtung im proximalen Flussfeld liegt, bestimmt und nicht die gleichen Geschwindigkeiten auf einer Hemisphäre (Abbildung 7).…”
unclassified